SUPPLIER EVALUATION AND SELECTION IN AGROINDUSTRIAL SUPPLY CHAIN MANAGEMENT OF GUAVA FRUIT JUICE (Case Study Guava Fruit Juice Industry PT XYZ, Subang, Jawa Barat) - Yusuf Andriana dan Taufik Djatna TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2012)
ABSTRACT Suppliers are important element to reduce cost of raw materials for agroindustrial supply chain management. This paper discusses a problem solving for the supplier’s evaluation and selection in agroindustry of guava juice. Contribution solution offered to guava juice agro industry that was obtained a systematic and objective procedures for choosing the right supplier by combining qualitative technique (Analytical Hierarchy Process) and quantitative technique (mixed integer programming). The objectives of this research were (1) to evaluate suppliers based on several criteria, i.e. price, product quality, delivery schedules, and showed history of product acceptance, (2) to apply an analytical model to minimize purchasing cost. The results showed that based on the evaluation of suppliers, there were three potential suppliers, and then from those was chosen supplier 3. The number of orders were 228.570 kg of guavaper year and total cost was Rp 481.517.906,63 per year. Keywords: suppliers evaluation ,guavafruit juice, AHP, mix integer programming